The Effect of Interactive Metalinguistic Feedback on the Iranian Middle School Students’ Argumentative Writing in English: A Mixed Methods Research - Aliakbar Tajik; Neda Hedayat; Neda Gharagozloo (Research in English Language Pedagogy, 2023)
The subject of corrective feedback in writing in English has always been a contentious issue among Second Language Acquisition (SLA) researchers despite an extensive body of research investigating the matter. This mixed-methods study aimed to examine the effectiveness of Interactive Metalinguistic Feedback (IMF) on the Iranian middle school students' ability in argumentative writing. To this aim, based on a multi-stage sampling, from 5 middle schools in Varamin, six classes were selected randomly; finally, 40 EFL students were sampled from the courses as the main participants of this study. A researcher-made writing test and a self-assessment questionnaire were utilized to collect the quantitative data.  The participants were grouped into Interactive Metalinguistic Feedback Class (IMFC) and Control Class (CC) and they were given a writing test as a pretest to ensure their homogeneity in terms of initial writing ability. After a 12-session treatment, a writing posttest was given to them. Furthermore, a self-assessment questionnaire was administered to collect data on students' attitudes toward the IMF in the learning-teaching process. To assemble the qualitative data, an interview accompanied by observation was conducted after the treatment to complement the quantitative results. The experimental findings of this current study revealed that IMF had a significant effect on the growth of argumentative writing ability among EFL students. The results of the qualitative part also indicated that social learning, situated learning, and dialogic interaction through IMF encouraged students to develop their writing skills as they co-constructed knowledge with others.